If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 8) + (-9x + 9) = 0 Reorder the terms: (8 + 8x) + (-9x + 9) = 0 Remove parenthesis around (8 + 8x) 8 + 8x + (-9x + 9) = 0 Reorder the terms: 8 + 8x + (9 + -9x) = 0 Remove parenthesis around (9 + -9x) 8 + 8x + 9 + -9x = 0 Reorder the terms: 8 + 9 + 8x + -9x = 0 Combine like terms: 8 + 9 = 17 17 + 8x + -9x = 0 Combine like terms: 8x + -9x = -1x 17 + -1x = 0 Solving 17 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 0 + -17 -1x = 0 + -17 Combine like terms: 0 + -17 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17
| x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x | | -3.2b+6=-5.1 | | 4(3x-1)=45 | | 2x^2+7=8x | | -5-2x+x=3 | | -2500-4.05=3000 | | -5(x+12)-13-=-24 | | 4.3b+5=8.1 | | 8.5x^3=79.687x+165.9891 | | 2x^2+7x-2=-2x^2+2x | | x^2+m+7=0 | | 7(x+2)+2=8 | | 5/7n-1=11 | | f(x)=x^5-3x^3+12x | | 3x+3-x=19 | | y+5=12*10 | | (9x+5)=(6x+5) | | 0.2a/4-10=2 | | -3(x-4)-15=-12 | | 2x-3=-7x+105 | | 50+3x^2=2 | | 30/20x=11/20 | | Y-6/y-2 | | f(t)=-16t^2+96t+3 | | a/6+2=4 | | 10x+20y+8=0 |